Clostridioides difficile infection following dental antibiotic prescriptions in a cohort of US veterans. (21st March 2023) - Wilson, Geneva M.; Evans, Charlesnika T.; Fitzpatrick, Margaret A.; Poggensee, Linda; Gibson, Gretchen; Jurasic, M. Marianne; Echevarria, Kelly; Suda, Katie J.
Abstract: Among 108 (0.05% of cohort) US veterans with a Clostridioides difficile infection (CDI) within 30 days of a dental antibiotic prescription, 80% of patients received guideline-discordant antibiotics. Half had chronic gastrointestinal illness potentially exacerbating their CDI risk. More efforts are needed to improve antibiotic stewardship.